Integrasi Nilai-Nilai Islam dalam Kurikulum Pendidikan: Studi Literatur pada Perspektif Pendidikan Berbasis Tauhid - Kholil, Muhammad Abu (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of this study is to analyze how Islamic values ​​can be effectively integrated into the curriculum to form a generation with Islamic character and excellence in various aspects of life. The method used in this study is a qualitative approach with literature studies, which refers to various reliable sources, including books, journals, and documents related to Islamic education based on monotheism. The results of the study indicate that monotheism-based education places the concept of monotheism as the main foundation in the formation of the curriculum. This can be seen from the integration of monotheism values ​​in the objectives, materials, methods, and evaluation of learning. The integration of Islamic values ​​includes cognitive, affective, and psychomotor aspects that focus on the formation of a complete human being (insan kamil) in accordance with Islamic teachings. The implementation of monotheism-based education also provides high relevance in facing the challenges of modernity, where moral and spiritual values ​​can be a foothold in the development of science. However, challenges such as the lack of understanding of educators regarding the concept of monotheism and resistance to curriculum changes are still obstacles that require collaborative solutions between the government, educational institutions, and the community. Thus, monotheism-based education is not only relevant in the context of Islamic education, but also has great potential to build a generation that is able to answer the needs of the times without losing Islamic values.